Assessment of genetic variability, correlation and path analysis for yield and its components in ajwain (Trachyspermum ammi L.) - S P Sharma, H K Jain, A Dashora, Ghanshyam Ghanshyam, N S Dodiya, (Journal of Spices and Aromatic Crops, 2015)
Genetic variability, heritability, correlation and path analysis were estimated among 28 germplasm for 10 characters in Ajwain (Trachyspermum ammi L.). Analysis of variance revealed significant differences among the germplasm lines for number of secondary branches plant-1, number of umbels plant-1, number of umbellets umbel-1, seed yield plant-1, harvest index and oil content, suggesting sufficient amount of variability in the experimental material. The estimates of genotypic coefficient variation (GCV) and phenotypic coefficient variation (PCV) indicated the existence of fairly high degree of variability for seed yield plant-1, oil content, number of umbels plant-1 and harvest index. Lower values of GCV and PCV were recorded in number of umbellets umbel-1 indicating the important role of environment in the expression of the characters. High heritability associated with moderate genetic advance was recorded in traits like harvest index and seed yield plant-1. The association study among characters revealed that seed yield was positively and significantly correlated with number of umbellets plant-1. Path coefficient analysis revealed that number of umbellets plant-1 had maximum positive direct effect on seed yield plant-1.